The Impact of Converting Fertile Land into Industrial Areas on Legal Justice for Local Communities in Brebes Regency - DIANITA NURUL ISLAMI (Law Research Review Quarterly, 2026)
The conversion of fertile land into industrial areas in Brebes Regency takes place through formal mechanisms stipulated in various land regulations. However, its implementation demonstrates an imbalance between the interests of economic development and the protection of community rights. This study aims to analyze the process of converting agricultural land into industrial areas and assess its legal implications for the justice of local communities. Using a qualitative approach with empirical juridical research, data were obtained through field observations, in-depth interviews with BPN officials and affected communities, and a review of relevant documents and regulations. The results indicate that although administrative procedures such as the issuance of KKPR/PKKPR, land acquisition, and technical verification have been implemented, the protection of productive land and the guarantee of farmers' rights have not been substantively fulfilled. Land conversion results in loss of livelihoods, decreased prod uctivity, social vulnerability, and legal uncertainty for the people of Brebes. These findings indicate that the principles of justice, sustainability, and people's prosperity as mandated by the UUPA and Article 33 paragraph (3) of the 1945 Constitution have not been fully realized in practice. Therefore, strengthening regulations and oversight mechanisms is necessary to ensure that industrial area development aligns with the protection of agrarian rights and legal justice for local communities.